2003
DOI: 10.1095/biolreprod.102.012674
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor in the Human Oviduct: Localization and Regulation of Messenger RNA Expression In Vivo

Abstract: In this study, we examined the localization of vascular endothelial growth factor (VEGF) and the changes in VEGF mRNA expression in various regions of the oviduct in fertile women throughout the ovulatory cycle. Oviduct tissue was collected from 22 women undergoing laparoscopic tubal sterilization or hysterectomy for a benign gynecological condition. Oviduct sections were divided into isthmus, ampullary, and infundibular regions. Serial cross sections were analyzed for the presence of VEGF by specific immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 31 publications
(40 reference statements)
4
31
0
2
Order By: Relevance
“…In vitro cultured murine follicles were engineered to secrete hormones in a manner that phenocopied the reproductive cycle (Skory et al, 2015) and were used to stimulate a physiological response in primary human fallopian tube tissue. In the co-culture system, the factors produced by the follicles during growth, ovulation and luteinization impacted fallopian tissue morphology and protein secretion, such as OVGP1, IGF1, VEGF-A and IL8, producing similar results to in vivo observations (Palter et al, 2001;Pushpakumara et al, 2002;Lam et al, 2003;Briton-Jones et al, 2004). In order to understand whether the dynamic changes of these factors in the reproductive cycle generated by the murine follicle were due to the steroid hormones, stepwise exogenous estrogen and progesterone were used to mimic the menstrual cycle steroid hormone patterns in our coculture system.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…In vitro cultured murine follicles were engineered to secrete hormones in a manner that phenocopied the reproductive cycle (Skory et al, 2015) and were used to stimulate a physiological response in primary human fallopian tube tissue. In the co-culture system, the factors produced by the follicles during growth, ovulation and luteinization impacted fallopian tissue morphology and protein secretion, such as OVGP1, IGF1, VEGF-A and IL8, producing similar results to in vivo observations (Palter et al, 2001;Pushpakumara et al, 2002;Lam et al, 2003;Briton-Jones et al, 2004). In order to understand whether the dynamic changes of these factors in the reproductive cycle generated by the murine follicle were due to the steroid hormones, stepwise exogenous estrogen and progesterone were used to mimic the menstrual cycle steroid hormone patterns in our coculture system.…”
Section: Discussionmentioning
confidence: 65%
“…A one-way ANOVA followed by Tukey's multiple comparisons test was used for statistical analysis, and P < 0.05 was considered statistically significant. enhance VEGF-A, but rather VEGF-A was induced by gonadotrophin hormones, such as rhFSH or hCG (Lam et al, 2003;. To test this, the fallopian tissue was cultured with either rhFSH or hCG for 6 days compared with the vehicle control, and the VEGF-A expression did not change in either of the treatments (Supplementary Figure 2).…”
Section: Factors Secreted From the Fallopian Tube Exhibit Cyclic Chanmentioning
confidence: 99%
See 1 more Smart Citation
“…The oviduct and the fluid contained within the oviduct provide a distinct microenvironment that influences sperm capacitation, final oocyte maturation, fertilization, and early embryo development [9]. Oviductal fluid is essential for the oviduct to carry out its reproductive functions [12]. Chemical analyses have indicated that oviductal fluid is a complex mixture of constituents derived from the plasma plus some specific proteins formed by the oviductal epithelium [13].…”
mentioning
confidence: 99%
“…Immunostaining of oviduct tissues from fertile woman undergoing tubal sterilization or hysterectomy detected VEGF protein in the oviduct luminal epithelium, smooth muscle cells, and blood vessels within the oviduct. VEGF mRNA expression was the highest during the periovulatory stage and was significantly correlated with LH concentration (Lam et al, 2003).…”
Section: The Impact Of Lh On Blood Vessel and Oviduct Physiologymentioning
confidence: 93%